Meningkatkan Kemampuan Menghafal Al-Qur’an dengan Menggunakan Metode Halaqah, Talqin, Murojaah di MI Al-Ma’shum Surakarta - Kinesti, Rakanita Dyah Ayu; Taufiqurrahman, Ariz Tri; Shofianur, Eva; Mu’jizah, Uyun (YASIN, 2023)
The focus of the research that will be tested in the study are: 1) The process of memorizing the Qur'an at MITTQUM 2) the application of methods for memorizing the Qur'an at MITTQUM 3) Factors supporting and hindering the Tahfidz Program. This study aims to describe the Qur'an memorization method applied by MI Tahfidzul Qur'an Integrated Al Ma'shum Surakarta and the constraints and supporting factors for the tahfidz program. This research uses a descriptive method with a qualitative approach. The research subjects are teachers and students. Collecting data using the method of observation, interviews and documentation. The results of this study found that the method of memorizing the Koran applied at MI Tahfidzul Qur'an Integrated Al Ma'shum Surakarta is the Halaqoh, Talqin and Muroja'ah methods. Factors supporting the Koran memorization program are conducive learning spaces, effective methods, competent teachers, rewards and support from parents who help the process of memorizing children at home and environmental factors. While the inhibiting factors are children who play or are sleepy in memorizing activities, long verses and busy parents so they don't have time to repeat the children's memorization at home.